181 Effects of Aspergillus oryzae prebiotic on energy and nutrient digestibility of growing pigs - Zhu, Jinlong (J Anim Sci, 2020)
The objective of this study was to determine the effects of an Aspergillus oryzae prebiotic (AOP, Amaferm(®)) on nutrient digestibility in growing pigs fed high fiber diets. Eighteen growing barrows (initial BW = 50.60 ± 4.90 kg) were surgically equipped with a T-cannula at the distal ileum. Three diets were formulated by including 29.65% corn-distillers dried grains with solubles (DDGS), 36.65% rice bran (RB) or 24.59% wheat middlings (WM) in corn and soybean meal-based diets to meet nutrient requirements for 50 to 75 kg growing pigs. Three additional diets were formulated by supplementing 0.05% AOP at the expense of corn in DDGS (DDGS + AOP), RB (RB + AOP), and wheat middlings (WM + AOP) diets. Pigs were allotted randomly to a triplicated 6 × 2 Youden square design with 6 diets and 2 successive periods. Feces and ileal digesta were collected for 2 d after a 21 d adaptation period, and nutrient content was analyzed to calculate apparent total tract digestibility (ATTD) and apparent ileal digestibility (AID). Standardized ileal digestibility (SID) of amino acids was calculated by correcting AID with basal endogenous amino acid losses determined from the same set of pigs. Supplementation of 0.05% AOP increased (P < 0.05) ATTD of DM, GE, CP, NDF, and ash in DDGS, RB, and WM diets. Diet DE was 35 kcal/kg greater (P < 0.05) in pigs fed AOP supplemented diets compared with those fed diets without AOP. Pigs fed DDGS+AOP diet had greater (P < 0.05) AID of ether extract compared to those fed DDGS diet. However, supplementation of AOP did not (P > 0.05) affect AID of GE, DM, CP, NDF, ash or SID of amino acids. In conclusion, supplementation of AOP in high fiber diets containing DDGS, RB, or WM increased total tract energy value and nutrient digestibility.